Artificial Intelligence in Retail: Benefits and Risks Associated With Mobile Shopping Applications - Victoria Stanciu; Sînziana-Maria Rîndașu (Amfiteatru Economic)
The objective of the study is to examine the practical implications of using artificial intelligence (AI) based solutions in the case of retail mobile applications, to enhance the online shopping experience and improve the engagement by also having in mind the privacy of the users. We examined 117 shopping applications available in the Google Play market and investigated the permissions required for each application and the categories of personal data collected from the users. Based on the information gathered, we provided practical methods to integrate artificial intelligence-based solutions to offer a new set of services, partially unavailable in physical stores. Some of the permissions identified, if exploited by malicious users, can affect individuals’ privacy. The fact that artificial intelligence is a fast-developing technology constitutes the main challenge in the effort of creating proper regulations. This research provides practical directions regarding the benefits of integrating artificial intelligence solutions in retail mobile applications in an ethical manner, protecting the users’ privacy.